Phillips curve in Brazil: an unobserved components approach - Machado, Vicente da Gama; Portugal, Marcelo Savino (Estudos Econômicos (São Paulo), 2014)
This paper estimates reduced-form Phillips curves for Brazil with a framework of time series with unobserved components, in the spirit of Harvey (2011). However, we allow for expectations to play a key role using data from the Central Bank of Brazil’s Focus survey. Besides GDP, we also use industrial capacity utilization rate and an unexplored time series (IBC-Br), as measures of economic activity. Our findings support the view that Brazilian inflation targeting has been successful in reducing the variance of both the seasonality and level of the inflation rate, at least until before the subprime crisis. Furthermore, inflation in Brazil seems to have responded gradually less to measures of economic activity in recent years. This provides some evidence of a flattening of the Phillips curve in Brazil, a trend previously shown by recent studies for other countries.